Letter (copy) - Probert, J. S.
041-0073-001 COPY. - Original taken by Dr. Morgan. 9, College Road, GUILDFORD, SURREY, 3.1.37. Sir W. Citrine, National Council of Labour, S.W.1. Sir, In response to your appeal in the "Daily Herald", I have no money to send but I offer my services in any capacity, such as, Ambulance or Lorry Driver, or Ambulance man, able to drive and repair any make of vehicle, and an excellent knowledge of minor wounds and injuries. Would gladly go to Spain if I would be of any use to you. I am, Yours truly, (Sgd) J.S. PROBERT. 292/946/41/73